2017
DOI: 10.1111/mmi.13777
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus nidulans BapH is a RAB11 effector that connects membranes in the Spitzenkörper with basal autophagy

Abstract: Using affinity chromatography we identified the Aspergillus nidulans F-BAR-and-PH domain-containing protein BapH as a RabE effector. BapH localizes to the Spitzenkörper (SPK) in an F-actin- and Sec7-dependent manner, becoming cytosolic after inactivation of Trs120 in TRAPPII, the oligomeric GEF for RabE . Therefore, RabE contributes to the recruitment of BapH to secretory vesicles in vivo. BapH has a close homologue, SlmA, which is related to yeast Slm1p/Slm2p, localizes to eisosomes and does not bind RabE . b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…These intermediates could be only a subpopulation of each domain, having specialized functions. In support of this, it has been shown that Slm1 of S. cerevisiae and its orthologue SlmA in A. nidulans are not found in all eisosomes or all MCTs, or even all MCL cortical foci (Berchtold et al 2012;Murley et al 2017;Pinar and Peñalva 2017;Busto et al 2018). Further work is needed in order to show whether PM domain intermediates or specialised subpopulations of PM domains exist, which could potentially serve specialized functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These intermediates could be only a subpopulation of each domain, having specialized functions. In support of this, it has been shown that Slm1 of S. cerevisiae and its orthologue SlmA in A. nidulans are not found in all eisosomes or all MCTs, or even all MCL cortical foci (Berchtold et al 2012;Murley et al 2017;Pinar and Peñalva 2017;Busto et al 2018). Further work is needed in order to show whether PM domain intermediates or specialised subpopulations of PM domains exist, which could potentially serve specialized functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the phylogenetic conservation of such a mechanism is not clear, since the homologues of the Slm proteins in S. pombe do not localize in eisosomes (Kabeche et al 2011). Similarly, SlmA of A. nidulans is only found at the eisosomes of the hyphae (Pinar and Peñalva 2017) and not at those of the head of the germlings, which respond to SL depletion (Athanasopoulos et al 2015). Differences in growth conditions and the existence of different populations of eisosomes with specialized roles (see paragraph 2.1.1) could potentially explain the apparent inconsistences.…”
Section: Mcc-mct -mentioning
confidence: 99%
“…BapH is an F‐BAR and PH domain containing protein that holds the honor of being the only bona fide RAB11 effector thus far characterized (Pinar & Peñalva, 2017). The domain composition of BapH suggests that it binds membranes with a certain degree of curvature.…”
Section: The “Canonical” Post‐golgi Rabs: Rab11 and Sec4mentioning
confidence: 99%
“…Standard A. nidulans media were used for strain propagation and conidiospore production [49,50]. Genetic techniques have been detailed [51].…”
Section: Aspergillus Media Culture Conditions and Transgenesmentioning
confidence: 99%